The ovo locus is required for sex-specific germ line maintenance in Drosophila. - Oliver, B.; Perrimon, N.; Mahowald, A.P. (Genes & Development, 1987)
Mutations at the ovo locus result in a defective female germ line. The male germ line is not affected. Adult females homozygous for loss-of-function alleles have no germ line stem cells. The sex-specific phenotype is evident at late blastoderm and early gastrula stages when the pole cells of embryos homozygous for a loss-of-function allele begin to die. This is the only zygotically acting gene known that is required specifically for embryonic germ line survival. Females heterozygous for dominant alleles or homozygous for alleles reducing gene activity exhibit a range of defects in oogenesis. We have mapped the ovo locus to position 4E1-2 of the salivary gland X chromosome by using a set of cytologically visible deletions.